The lived experiences of the impoverished elderly - Li, Julius (2017)
How does one spend old age in impoverishment? How did they end up in this predicament? This study aims to examine the trajectories of old people who live in heavily subsidized housing and attempts to identify patterns of structural influence and personal agency. Another area of focus for this study is the demographic of the single elderly. Marriage rates are on the decline in Singapore, this coupled with an aging population mean that elderly who are single may be on the rise. However this study also includes widows and widowers. As such this study also examines relationships and sources of support in late life. (9669 words)